328 INCREASED DIETARY PROTEIN AS CASEIN BUT NOT SOY AUGMENTS RENAL ENDOTHELIN PRODUCTION. (1st January 2005) - Nathan, T.; Rose, T.; Khanna, A.; Hacker, C.; Simoni, J.; Duran, M. J.; Wesson, D. E.
Abstract : Increased dietary protein provided as purified casein augments renal endothelin production (JASN 2004;15:2266) by mechanisms that have not been fully elucidated. We tested the hypothesis that augmented renal endothelin production induced by dietary protein as casein is mediated by the acid challenge to systemic acid-base status induced by metabolism of this protein source. Munich-Wistar rats ate minimum electrolyte diets with protein provided as either casein (CAS) that yields net acid or soy that yields net base when metabolized. After 3 weeks of diet we measured blood and urine acid-base data, urine endothelin-1 (ET-1) excretion as a surrogate of renal ET-1 production, and renal cortical endothelin-1 mRNA with real-time PCR and light cycler technology. Within groups eating the two protein types, those eating diets with higher protein content (50%) were compared to those eating 20% protein, the latter % being comparable to standard rat chow. Animals eating 50% compared to 20% CAS had lower serum total CO2 (23.3 ± 0.5 vs. 25.2 ± 0.6 mM, p < .03), higher urine net acid excretion (NAE) (7067 ± 937 vs. 4460 ± 639 μM/d, p < .04), and higher urine ET-1 excretion (70 ± 14 vs. 22 ± 3 pg/day, p < .005). By contrast, total CO2 (27.3 ± 0.6 vs. 26.6 ± 0.7 mM, p = .78), urine NAE (1698 ± 247 vs. 1803 ± 332 μM/d, p = .80), and urine ET-1 excretion (42 ± 10 vs. 37 ± 3 pg/day, p = .64) were not higher in animals eating 50% compared to 20% soy. ET-1 mRNA was higher in 50% vs. 20% CAS but was similar in 50% vs. 20% soy. 50% CAS animals given oral bosentan, an endothelin A/B receptor antagonist, had higher serum total CO2 (24.8 ± 0.5 vs. 23.3 ± 0.4 mM, p < .04, paired t) and lower urine NAE (7067 ± 937 to 5704 ± 594 μM/d, p < .05, paired t) than 50% CAS animals not given bosentan. Serum total CO2 and urine NAE were not different in the bosentan-ingesting vs. non-ingesting 20% CAS or in either soy group. The data show that increasing dietary protein with the acid-producing casein diet but not with the base-producing soy diet increases renal endothelin production and induces endothelin-mediated augmentation of renal acidification. The data support the hypothesis that augmented renal endothelin production induced by increased dietary protein as casein is medicated through the acid challenge to systemic acid-base status provided by the casein diet.